Anti-Eosinophil Biologics in Chronic Respiratory Diseases - Wu, Huizi; Huang, Lan; Liu, Yan (Journal of Contemporary Medical Practice, 2024)
Eosinophils play a crucial role in the pathogenesis of various chronic respiratory conditions. Recent advances in understanding eosinophilic inflammation have promoted the development of biologics aimed at specifically targeting inflammation driven by eosinophils. One such biologic, benralizumab, has shown considerable efficacy and favorable tolerability in individuals with refractory eosinophilic asthma. While the efficacy of these therapies in COPD is less consistent, promising results have been observed in specific eosinophilic subtypes. For CRSwNP, biologics have shown potential in reducing nasal polyp size, alleviating clinical symptoms, and decreasing the need for surgical intervention. In spite of these therapeutic advancements, challenges remain, including high treatment costs and a lack of long-term safety data. Future research should prioritize biomarker identification to optimize patient selection and further individualize these therapies.